Fermented rice-bran by Saccharomyces cerevisiae: Nutritious ingredient in the formulation of gluten-free cookies. (April 2021) - Christ-Ribeiro, Anelise; Chiattoni, Lidiane Moreira; Mafaldo, Claudia Roseli Fagundes; Badiale-Furlong, Eliana; Souza-Soares, Leonor Almeida de
Abstract: Rice bran is rich in protein, lipid and other nutrients. The objective was to evaluate the effect of rice flour and rice bran fermented by Saccharomyces cerevisiae in gluten free cookies formulation, as well to characterize them for their physicochemical and antioxidant properties, sensory and microbiological. The formulations were elaborated with different levels of rice bran fermented (25 g, 50 g and 100 g, or 7.08%, 14.16% and 28.33%, respectively) besides rice flour, control (without it) and other ingredients. The proximate composition, phenolic profile and antioxidant activity, sensory analysis and shelf life were determined in formulations. The use of fermented-rice bran show to be a potential substitute for wheat flour in cookie making. All formulations presented higher protein level, phenolic compounds and their antioxidant activity, and shelf life was 90 days. The cookies also presented good sensory attributes and acceptability by the consumer, highlighting the formulation of 25 g fermented-rice bran. The use of rice bran fermented by S. cerevisiae proved to be a potential alternative as an ingredient in the preparation of gluten-free cookies. Highlights: Fermented rice bran as an alternative ingredient for celiacs. High protein cookies and phenolic compounds. Phenolic compounds, their profile and antioxidante actives compareted (PCA).